Barriers to Knowledge Management in the Health Sector of Pakistan - Karamat, Jawad; Shurong, Tong; Ahmad, Naveed; Waheed, Abdul; Khan, Shahbaz (Sustainability, 2018)
Knowledge management (KM) is the source for creating a sustainable competitive advantage, and it helps the organizations to retain, develop, organize and utilize their knowledge. Due to globalization, the organizations must maintain their knowledge assets to survive. Many organizations have realized the potential of KM and are applying it. Since the healthcare industry is growing significantly, it is continuously generating a wealth of knowledge. This knowledge can be recorded, communicated and used by many health care professionals with the help of KM. There is a wealth of research on KM in healthcare of developed countries, but very few studies regarding KM implementation can be found in developing countries i.e., Pakistan. Pakistan is now looking towards the implementation of KM; it is in its initial stages. The implementation of KM in the healthcare of Pakistan is affected by different barriers. In this study, the barriers will be identified and analyzed. An interrelationship between the barriers will be determined, and how the different barriers support each other (driving power), and how they influence each other (dependence power). The results of interpretive structural modeling (ISM) and MICMAC (Matrice d’Impacts croises-multipication appliqué an classment i.e., cross-impact matrix multiplication applied to classification) approach show that lack of support from top management, insufficient strategic planning and lack of support from organizational structure are the main barriers to KM adoption in the healthcare of Pakistan. This study provides a solution in determining the main barriers that need to be solved first, and to ensure effective implementation of KM in the healthcare of Pakistan.